The disruptive role of LRG1 on the vasculature and perivascular microenvironment - Dritsoula, Athina; Camilli, Carlotta; Moss, Stephen E.; Greenwood, John (Frontiers in Cardiovascular Medicine, 2024)
The establishment of new blood vessels, and their subsequent stabilization, is a critical process that facilitates tissue growth and organ development. Once established, vessels need to diversify to meet the specific needs of the local tissue and to maintain homeostasis. These processes are tightly regulated and fundamental to normal vessel and tissue function. The mechanisms that orchestrate angiogenesis and vessel maturation have been widely studied, with signaling crosstalk between endothelium and perivascular cells being identified as an essential component. In disease, however, new vessels develop abnormally, and existing vessels lose their specialization and function, which invariably contributes to disease progression. Despite considerable research into the vasculopathic mechanisms in disease, our knowledge remains incomplete. Accordingly, the identification of angiocrine and angiopathic molecules secreted by cells within the vascular microenvironment, and their effect on vessel behaviour, remains a major research objective. Over the last decade the secreted glycoprotein leucine-rich α-2 glycoprotein 1 (LRG1), has emerged as a significant vasculopathic molecule, stimulating defective angiogenesis, and destabilizing the existing vasculature mainly, but not uniquely, by altering both canonical and non-canonical TGF-β signaling in a highly cell and context dependent manner. Whilst LRG1 does not possess any overt homeostatic role in vessel development and maintenance, growing evidence provides a compelling case for LRG1 playing a pleiotropic role in disrupting the vasculature in many disease settings. Thus, LRG1 has now been reported to damage vessels in various disorders including cancer, diabetes, chronic kidney disease, ocular disease, and lung disease and the signaling processes that drive this dysfunction are being defined. Moreover, therapeutic targeting of LRG1 has been widely proposed to re-establish a quiescent endothelium and normalized vasculature. In this review, we consider the current status of our understanding of the role of LRG1 in vascular pathology, and its potential as a therapeutic target.